2022
DOI: 10.1055/s-0042-1751366
|View full text |Cite
|
Sign up to set email alerts
|

Pd/RHA and Pd/BPA as Eco-Friendly Heterogeneous Catalysts: Microwave-Assisted C–S Cross-Coupling Reaction in DMF

Abstract: First time, Pd-Rice Husk Ash (Pd/RHA) and Pd-Banana Peel Ash (Pd-BPA) were used as eco-friendly catalysts in the C–S cross-coupling reaction of 5-bromo-2,1,3-benzothiadiazole with various benzene thiols in DMF under microwave irradiation at 75 °C, 200 W (100 psi) for 15–25 min. These catalysts were produced from agro-industrial wastes, such as rice husk ash and banana peel ash. These can be recycled and reused up to five catalytic cycles without loss of catalytic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It was remarkable that reaction at room temperature was seen in the case of 5-bromobenzo­[ c ]­[1,2,5]­thiadiazole, while this coupling reaction with thiols under the catalysis of Pd complexes was specially investigated in a recent paper to examine the fluorescent properties of related coupling products . Our observation demonstrated that no catalyst was needed for this transformation ( 7l ).…”
Section: Resultsmentioning
confidence: 81%
“…It was remarkable that reaction at room temperature was seen in the case of 5-bromobenzo­[ c ]­[1,2,5]­thiadiazole, while this coupling reaction with thiols under the catalysis of Pd complexes was specially investigated in a recent paper to examine the fluorescent properties of related coupling products . Our observation demonstrated that no catalyst was needed for this transformation ( 7l ).…”
Section: Resultsmentioning
confidence: 81%
“…The above-mentioned reports contain drawbacks, such as the use of hazardous reagents, solvents, expensive catalysts, prolonged reaction times, high temperatures, and harsh reaction conditions, as well as the formation of unwanted products. The methodologies employing green catalysts, such as non metal salts, heterogeneous recyclable catalysts, or ionic liquids, [44][45][46][47][48][49][50][51] and green solvents, or solvent-free or microwave or ultrasonic conditions [52][53][54] , are desirable to promote sustainable ecofriendly research. [55][56][57] In this regard, ionic liquids (ILs) have shown promising results in a variety of synthetic processes because of their great selectivity and catalytic efficiency.…”
Section: Template For Synopen Thiemementioning
confidence: 99%